Analysis of invalid votes in the village head elections in Purbalingga Regency, Indonesia - Akbar, Andi Ali Said; Handoko, Waluyo; Nurprojo, Indaru Setyo; Perdani, Titis (Department of Government Studies, Universitas Muhammadiyah Makassar, 2025)
This study analyzes the causes of the large number of invalid votes during village head elections. Political scientists have pay little attention to this phenomenon. This study uses a case study method to examine why and how this situation occurred. Data were obtained through in-depth interviews with 17 people in three villages and document studies. Informants included village head candidates, election committees, election supervisors, and winning teams. The study found that the number of invalid votes was very high, at 18%, 21%, and 29% because of symmetrical votes, i.e., two parallel holes. Invalid votes occurred due to three factors: sociological factors, such as low voter knowledge; political protest as a means of political criticism; and institutional factors, such as weak regulations and low committee competence. This occurred due to institutional factors, such as diverse interpretations of regulations regarding valid votes, poor ballot design, and incompetent election committees. This research contributes to promoting improvements in voting regulations that accommodate symmetrical votes, designing secure ballots for voters, and encouraging committees to intensively socialize voting procedures.